The Degree of use of the Aurasma program in Damascus and its Difficulties in Kindergartens in Damascus (Journal of Hama University, 2021)
The aim of the research was to identify the degree of use of the Aurasma program in the educational process in kindergarten in the city of Damascus, and to identify the difficulties that limit the use of kindergarten teachers for it, and to identify the effect of a variable (years of experience and educational qualification) on the use of kindergarten teachers for the program of Aurasma. The researcher has prepared a questionnaire to know the views of a sample of kindergarten teachers in the city of Damascus, numbering (73) female teachers, and the questionnaire consisted of four axes on a five-point scale, the first and second axes relate to the degree of use, and the third and fourth axes relate to difficulties.  The results of the research showed that the use of kindergarten teachers for the Aurasma program came with a very little degree that is almost nonexistent, and the most important difficulties that limit the use of kindergarten teachers for the Aurasma program were poor internet, ignorance of the teachers in the program and the lack of a technical expert in the kindergarten, in addition to weak encouragement by management and the small number of smart devices in the stage of kindergarten. The results also showed that there are statistically significant differences between the averages of the kindergarten teachers ’answers to the questionnaire attributable to the variable of the academic certificate in favor of the higher qualification which is postgraduate studies, in addition to the presence of statistically significant differences between the averages of the kindergarten teachers’ answers due to the variable number of years of experience in favor of those with five experience Years and less.